Spatial analysis of ischemic stroke in Spain: the roles of accessibility to healthcare and economic development - Leveau, Carlos Marcelo (2024)
Ischemic Stroke (IS) is a major cause of mortality worldwide; however, few studies have been carried out to measure the impact of the distribution of healthcare services on IS lethality.The aim of this study was to explore the relationship between three IS outcomes (incidence, mortality, and lethality) and accessibility to hospitals in Spain, considering the economic development.A cross sectional ecological study was performed using data capturing all hospital admissions and mortality due to IS during 2016–2018. Gross Geographic Product per capita (GGPpc) was calculated and a healthcare accessibility index was created. A Besag-York-Molliè autoregressive spatial model was used to estimate the magnitude of association between IS outcomes and economic development and healthcare accessibility. GGPpc showed a geographical gradient from southwest to northeast in Spain. Mortality and lethality rates due to IS were higher in the south of the country in both women and men aged 60+ years. In women and men aged 20-59 years a 1,000 € increase in GGPpc was associated with decreases in mortality of 5% and 4%, respectively. Lethality decreased 3-4% with each 1,000 euro increase of GGPpc in both sexes and in the 20-59 and 60+ age groups. Decreased healthcare accessibility was associated with higher lethality in the population aged 60+.Economic development in southwest Spain would not only improve employment opportunities but also reduce mortality due to IS. New health related strategies to improve hospital accessibility should be considered in regions more sparsely populated or with worse transport and/or healthcare infrastructure.